Analisis Sistem Kemitraan Usaha Ayam Broiler dalam Perspektif Manajemen Bisnis Syariah (Studi Kasus Kemitraan Peternakan Eka Asenk di Pasaman Timur) - Gusriandi; Aidil Alfin (ARZUSIN, 2026)
Although broiler farming partnership systems have been widely studied because of their role in increasing farm productivity and expanding farmers’ access to production inputs and marketing, research analyzing their implementation based on the principles of Sharia Business Management, particularly justice, transparency, and syirkah, remains limited. This study aimed to analyze the broiler farming partnership system at Eka Asenk Farm from the perspective of Sharia Business Management. This study employed a qualitative approach with a descriptive design. The research informants consisted of the owner of Eka Asenk Farm, farm employees, and technical service personnel from PT Pokphand, who were selected based on their direct involvement in the implementation of the partnership. Data were collected through observation, interviews, documentation, and a literature review and were subsequently analyzed through data reduction, data display, and conclusion drawing. The results showed that the nucleus–plasma partnership model facilitated farmers through the provision of production inputs, technical assistance, and guaranteed marketing of harvest yields. However, its implementation did not fully reflect the principles of Sharia Business Management because imbalances in profit sharing, limited technical assistance, and farmers’ high dependence on the nucleus company remained. These findings enrich the literature on Sharia Business Management, particularly regarding the application of the concept of syirkah in livestock farming partnerships. This study emphasizes the need to improve transparency, balance rights and obligations, and refine profit-sharing mechanisms to establish partnerships that are equitable, sustainable, and compliant with Sharia principles. Future research is recommended to involve more diverse locations and employ a mixed-methods approach to obtain a more comprehensive understanding.